Preliminary evaluation of [18F]AlF-NOTA-MAL-Cys39-exendin-4 in insulinoma with PET. (21st October 2015) - Xu, Qing; Zhu, Chen; Xu, Yuping; Pan, Donghui; Liu, Ping; Yang, Runlin; Wang, Lizhen; Chen, Fei; Sun, Xinchen; Luo, Shineng; Yang, Min
Abstract: Background : High expression of glucagon-like peptide-1 receptor (GLP-1R) in insulinoma supplies a potential drug target for tumor imaging. Exendin-4 can specifically bind to GLP-1R as an agonist and its analogs are extensively used in receptor imaging studies. Purpose : A new GLP-1R imaging agent, [ 18 F]AlF-NOTA-MAL-Cys 39 -exendin-4, was designed and prepared for insulinoma imaging. Methods : Cys 39 -exendin-4 was conjugated with NOTA-MAL, then the compound was radiolabeled with [ 18 F]AlF complex to obtained [ 18 F]AlF-NOTA-MAL-Cys 39 -exendin-4. The tumor-targeting characters of the tracer were evaluated in INS-1 cells and BALB/c nude mice models. Results : [ 18 F]AlF-NOTA-MAL-Cys 39 -exendin-4 can be efficiently produced with a yield of 17.5 ± 3.2% (non-decay corrected) and radiochemical purity of >95%. The IC50 value of displacement [ 18 F]AlF-NOTA-MAL-Cys 39 -exendin-4 with Cys 39 -exendin-4 was 13.52 ± 1.36 nM. PET images showed excellent tumor visualization with high uptake (9.15 ± 1.6%ID/g at 30 min and 7.74 ± 0.87%ID/g at 60 min). The tumor to muscle, pancreas and liver ratios were 63.25, 3.85 and 7.29 at 60 min after injection. GLP-1R binding specificity was demonstrated by co-injection with an excess of unlabeled Cys 39 -exendin-4 and the tumor uptake was found to be reduced significantly. Conclusion : [ 18 F]AlF-NOTA-MAL-Cys 39 -exendin-4 shows favorable characteristics for insulinoma imaging and may be translated to clinical studies.